Peran Kualitas Audit dalam Memoderasi Pengaruh Kebijakan Pembayaran Dividen terhadap Nilai Perusahaan - Padya, Handini Nara; Wijayanti, Rita (Jurnal EMT KITA, 2026)
Developments in the capital market require companies to enhance corporate value as a key indicator of performance and investment appeal. Dividend payment policies are often viewed as a positive signal by investors, while audit quality is expected to enhance the credibility of financial statements. However, the role of audit quality in strengthening the relationship between dividend policy and corporate value has yet to yield consistent results, particularly in the property and real estate sector. This study aims to examine and analyze the impact of dividend payment policies on corporate value and to test the moderating role of audit quality in this relationship among companies in the property and real estate subsectors listed on the Indonesia Stock Exchange during the 2020–2023 period. This study uses secondary data in the form of annual financial statements obtained from the Indonesia Stock Exchange, the companies’ official websites, and supported by data from IDN Financial. The research sample was determined using purposive sampling. The analytical methods used include descriptive statistics, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple regression analysis. The results indicate that dividend payment policies have a significant effect on firm value. Audit quality does not moderate the relationship between dividend payment policies and firm value. This suggests that the market places greater emphasis on dividend payout decisions as a direct indicator of firm performance than on audit quality as a moderating variable.